Growth of barrier-type anodic films on magnesium in ethylene glycol electrolytes containing fluoride and water. (10th October 2015) - Habazaki, Hiroki; Kataoka, Fumitaka; Shahzad, Khurram; Tsuji, Etsushi; Aoki, Yoshitaka; Nagata, Shinji; Skeldon, Peter; Thompson, George E.
Abstract: This study demonstrates the formation of uniform barrier-type anodic films on magnetron-sputtered magnesium films at high current efficiency in ethylene glycol electrolytes containing 0.1 mol dm −3 NH4 F and various concentrations (0.1–28 mol dm −3 ) of H2 O. The anodic films containing a crystalline MgF2 phase develop both at the metal/film and film/electrolyte interfaces due to simultaneous migrations of anions inwards and cations outwards, respectively. When a Mg −1.2 at% Au/Mg bilayer film is anodized, initial prior oxidation of magnesium proceeds with gold atoms accumulating in a thin layer beneath the anodic film. The accumulated gold atoms are incorporated into the anodic film as a band when the alloy layer is completely anodized. Fluoride-containing gold species are formed by the incorporation and the gold species migrate outwards at a rate of 0.4 times the rate of Mg 2+ ions. The addition of phosphate in the electrolyte results in the formation of an amorphous anodic film, and the phosphate incorporated into the anodic film is distributed throughout the film thickness. The transport number of cations is also influenced by the phosphate incorporation.